MODEL PENDIDIKAN MORAL ANAK JALANAN DI SURAKARTA - Badrus Zaman (Program Studi Manajemen Pendidikan, 2019)
The purpose of this study was to determine the model of moral education given by the PPAP Seroja institution to street children in Surakarta, as well as what factors influenced the difficulty of implementing moral education in the PPAP Seroja Surakarta institution. This research is field research (Field Research) that is research conducted directly with the object of research and conducted data collection in the field. This type of research is a descriptive qualitative study conducted at PPAP Seroja Surakarta in 2019, data collected through the method of observation, documentation, and interviews. The analysis was performed using interactive analysis. The conclusions of the study are as follows: the moral education model applied in the PPAP Seroja Surakarta institution using the lecture model, counseling model, model, skills model, and model outing class. Whereas the factors that hinder the implementation of moral education on the moral development of street children in PPAP Seroja Surakarta are the factors of street children who are still lack of interest in street children and tend to be lazy in following moral education, in addition to the factors of mentors who are less competent in delivering moral education material. because the methods used tend to be monotonous so that street children get bored easily, the lack of supporting infrastructure and a less supportive family environment, and less motivation to give street children a moral education.